Explanations without a purpose? Genre-based instruction and academic writing - Ting, Su Hie; Campbell, Yvonne Michelle; Law, Lily; Poh, Hua Ho (Association for Academic Language and Learning (AALL), 2013)
The study examined the structure and language features of explanation texts written by university students who have been taught academic writing through the principles of genre-based instruction. Students enrolled in an English for Academic Purposes (EAP) course at a Malaysian university were asked to write an explanation of a natural phenomenon in a text-to-diagram task. The analysis of 100 explanation texts showed that the sequential explanation of how a natural phenomenon occurs inevitably involves an account of the causal connection between the events. Text structure-wise, the students were able to sequence the events and the only weakness was the tendency to omit the statement of text purpose. These results indicate that some elements of conventions of text structure may be more difficult to acquire than language features despite explicit teaching using the genre-based approach. The orderly sequencing of events was achieved through the use of many connectors, predominantly sequential connectors and less causal connectors but the range was limited. The three most commonly used connectors were “then”, “after” and “when”. In their explanations, the students also used some passives as is characteristic of the explanation genre but the construction was often inaccurate. Most of the students used the present tense to show the timelessness nature of the phenomenon but a quarter of the verbs were written in the future tense. The study also found that poor language competence prevents students from writing good explanations.